Programação em par: investigando sua eficácia perante tarefas de modelagem e construção de software - Lima, Vagner Carlos Marcolino (2013)
Among eXtreme Programming (XP) practices, Pair Programming(PP) stands out from the rest. It consists of two individuals cooperating, working in the same task - design, algorithm, code or test - in the same computer. The general objective of this study is to scrutinize the efficacy of Pair Programming versus individual programming relating to modeling tasks and object oriented software development. The efficacy of the process is evaluated through the following software quality related attributes: (i) method size, (ii) structural complexity of the methods, (iii) linkage/dependency among packages and finally (iv) lack of cohesion of the methods by class. Therefore, an experimental research was performed, involving practical activities and surveys answered by volunteer students from three different higher education institutions in Curitiba. This research showed that pair programming is more efficient when working with modeling tasks and software development than individual programming, taking into account size and complexity of methods. Furthermore, more pros than cons were found by students when pair programming was chosen to accomplish such tasks.